The Influence of Individual Characteristics and Ethical Behavior on Employee Performance Mediated by Organizational Commitment - Nyimas Fitri Yulianingrum; Muchlis Mas'ud; Survival (Optima Science, 2024)
This study aims to obtain empirical evidence of the influence of individual characteristics and ethical behavior on employee performance mediated by organizational commitment. The population in this study were all employees of the Regional Secretariat of Probolinggo City, totaling 147 people. The determination of the number of samples using the Slovin formula, which is 96 people. The data analysis technique used in this study is Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS software version 4.0. The results of the study indicate that better individual characteristics can encourage increased employee performance. Better individual characteristics can encourage increased organizational commitment. Better ethical behavior can encourage increased employee performance. Better ethical behavior can encourage increased organizational commitment. Higher organizational commitment can encourage increased employee performance. Organizational commitment plays a role in mediating part of the influence of individual characteristics on employee performance. Organizational commitment plays a role in mediating part of the influence of ethical behavior on employee performance.